ANALISIS HUKUM PELAKSANAAN PENYELESAIAN SENGKETA BISNIS DENGAN METODE ARBITRASE ONLINE DI INDONESIA DAN DI SINGAPURA - Yongky Pieter Lahema (2021)
Online arbitration has been carried out by the Singapore International Arbitration Center (SIAC), then SIAC Rules, Arbitration Act of Singapore, and UNCITRAL as a legal basis SIAC already has rules regarding online arbitration. The Indonesian National Arbitration Board (BANI) has practically carried out online arbitration, but the BANI Arbitration Rules & Procedures and Law No.30 of 1999 as the legal basis for BANI do not have clear rules. This writing will discuss the comparison of online arbitration enforcement at SIAC with BANI, how SIAC regulates online arbitration execution and whether it can be adopted for online arbitration arrangements at BANI. This research was conducted using a normative juridical method. The approach used is legislation and comparison. The results of the comparative research on the implementation of online arbitration at SIAC and BANI show that SIAC already has rules that clearly regulate the implementation of online arbitration from arbitration registration, hearings, to online arbitration awards. In the implementation of online arbitration at BANI, BANI online arbitration registration is possible because it has the rules, but in the subsequent process of online examination hearings, and online arbitration awards do not yet have rules that regulate explicitly and clearly. Online arbitration arrangements at SIAC can be adopted into online arbitration procedure law by BANI and the Indonesian Arbitration Law because they do not conflict with other laws in Indonesia.